2023
DOI: 10.1097/tp.0000000000004416
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Heart Transplantation Using a Temperature-controlled Hypothermic Storage System

Abstract: Background. The SherpaPak Cardiac Transport System is a novel technology that provides stable, optimal hypothermic control during organ transport. The objectives of this study were to describe our experience using the SherpaPak system and to compare outcomes after heart transplantation after using SherpaPak versus the conventional static cold storage method (non-SherpaPak). Methods. From 2018 to June 2021, 62 SherpaPak and 186 non-SherpaPak patients underwent primary heart transplantation at Stanford Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…8 Additional single center analysis also found similar results with additional findings of less need for blood products perioperatively and shorter ICU length of stay. 3,4 Lastly, registry analysis of more than 12 hospitals found that with improved clinical outcomes, hospital care costs were reduced by more than $26,000 dollars per patient. 9 Thus, the clinical and financial benefit of SCTS is becoming more evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Additional single center analysis also found similar results with additional findings of less need for blood products perioperatively and shorter ICU length of stay. 3,4 Lastly, registry analysis of more than 12 hospitals found that with improved clinical outcomes, hospital care costs were reduced by more than $26,000 dollars per patient. 9 Thus, the clinical and financial benefit of SCTS is becoming more evident.…”
Section: Discussionmentioning
confidence: 99%
“…2 Prior studies have demonstrated that the SCTS provides safe outcomes with respect to PGD and mortality. 3,4 However, to date, no studies have identified outcomes with respect to the relationship between elevated dd-cfDNA scores and different transportation methods including SCTS and ice.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective single-center experiences with Sherpapak technology have been reported by a small number of centers in recent years. [13][14][15][16][17] Early results from the GUARDIAN Registry were presented at the 2022 annual meeting of the International Society of Heart and Lung Transplantation. 18 At that time, the registry included data from 11 participating heart transplant centers in the United States, with a cohort of 156 patients receiving organs preserved with conventional cold storage (control), and 227 receiving organs preserved with the SherpaPak.…”
mentioning
confidence: 99%
“…Retrospective single-center experiences with Sherpapak technology have been reported by a small number of centers in recent years. 13–17…”
mentioning
confidence: 99%
“…In this edition of the journal, Zhu and colleagues from Stanford University report their experience with the Paragonix SherpaPak temperature-controlled hypothermic storage system for donor heart preservation and transport. 7 Its main stated advantage over traditional static cold storage (SCS) is more precise temperature control during transport with the heart maintained between 4.5° and 6.5° centigrade. The authors switched from SCS to using the SherpaPak system (Paragonix Technologies, Cambridge, MA) in June 2020.…”
mentioning
confidence: 99%